PENERAPAN COMMUNITY BASED TOURISM DALAM PENGELOLAAN WISATA BERKELANJUTAN DI KAMPUNG GENTENG CANDIREJO - Ertien Rining Nawangsari; Muhammad Zaky Dharmawan; Nur Sabrina Hana Afifah; Nisrinada Zahirahaini Fajrin (Journal Publicuho, 2021)
Kampung Genteng Candirejo is a village that is included in the category of tourist villages in Surabaya. Kampung Genteng Candirejo is characterized by its processing of herbal products and environmental-based village management to achieve sustainable tourism management. The development of Kampung Genteng Candirejo as an alternative for tourism involves community participation in the formation of tourism village institutions as well as the existence of herbal product business units that can improve the community's economy. The purpose of this research is to identify the management of Kampung Genteng Candirejo in the perspective of community based tourism as sustainable tourism. The method used in this research is descriptive qualitative using the theory of community based tourism. Data collection techniques are carried out through observation, interview and documentation techniques. The results showed that community based tourism has been applied to tourism management in Genteng Candirejo Village, the application of community based tourism is applied in the form of active community participation, the formation of tourism village management agencies, the existence of herbal product processing business activities that improve the community's economy, and village management through an environmentally friendly program.